Sustainable energy - Dunlap, Richard A. (Cengage Learning, 2015)
The book approaches these topics on a rigorous level -- familiarity with the basic concepts of freshman Physics and Chemistry is needed. The book contains enough material for a typical one semester course. The end-of-chapter problems are predominantly quantitative in nature. However, most are not straight forward calculations based on substituting values from the chapter in to the appropriate formula